2012
DOI: 10.1039/c2ob26241j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental exploration of the photochemistry of resveratrol: beyond the simple double bond isomerization

Abstract: The photochemical isomerization of resveratrol has been the subject of recent studies in which contradictory results were reported. The photoproduct mixture of this reaction needs to be considered more complex than the coexistence of cis and trans isomers. An unidentified third product, at least, has been detected in various studies although its nature was unknown. In this work, we aim to provide a thorough description of the photochemical course of this reaction through experimental and computational approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…However, none of these authors could unequivocally characterize all the photoproducts [7][8][9][10][11][12]. Many of them started by indirect experiments aimed to compare the photochemical reaction kinetics of stilbenes to that of resveratrol.…”
Section: Photochemistry Of Resveratrol Iso-merizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of these authors could unequivocally characterize all the photoproducts [7][8][9][10][11][12]. Many of them started by indirect experiments aimed to compare the photochemical reaction kinetics of stilbenes to that of resveratrol.…”
Section: Photochemistry Of Resveratrol Iso-merizationmentioning
confidence: 99%
“…However, in spite of the absence of unequivocal spectral data, the formation of THDHP intermediate during resveratrol photochemical oxidation-reaction is accepted by the scientific community and supported by UV-Vis, fluorescence data and spectral studies on stilbenes [9,12]. Firstly, in the case of resveratrol the solvent applied for the reaction should be less hydrophobic than those utilized for stilbene photoconversion, due to the presence of the three -OH groups on the aromatic rings that give an important contribution to the solubility of resveratrol in more polar solvents.…”
Section: Photochemistry Of Resveratrol Iso-merizationmentioning
confidence: 99%
“…The formation of a trihydroxy phenanthrene was supported also by Tříska et al [17] Yang et al [18] showed that the UV irradiation of trans-resveratrol leads to the formation of a highly fluorescent compound, resveratrone, which was properly characterized by UV, MS and NMR. Computational exploration by Rodríguez et al [19] uncovered the feasibility of singlet oxygen addition to cis or trans-resveratrol to furnish a dioxetane intermediate which spontaneously cycloreverts to benzaldehydes. Recently, Francioso et al [20] showed that upon UV-exposure resveratrol in red wine can isomerise from the trans to the cis-isomer, which may further cyclise to 2,4,6-trihydroxyphenanthrene.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for photoinduced trans - cis isomerization of resveratrol. Moreover, once the cis -isomer is formed it is possible to form the phenanthrene-derivative by energy-consuming ring closure, a chemical-quenching mechanism ( Figure 5 B) [ 58 , 59 , 60 ]. The cis -isomers of a series of chlorine substituted stilbenes have been prepared by irradiating solutions of the trans -isomers [ 61 ].…”
Section: Discussionmentioning
confidence: 99%